2010
DOI: 10.1007/s10694-010-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Performance of Fire Detection Systems for Tunnel Applications––Part 2: Full-Scale Experiments Under Longitudinal Airflow Conditions

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Each sense cable of the system is required to cover two traffic lanes in the tunnels. Many researches have been conducted to study their capability and limitation in tunnel environments [29][30][31][32]. Test and operation results show that the linear heat detection systems:  Respond to a fire at its flame stage as the temperature in the tunnel raises, which may miss early warnings of the fire, depending on the fire type.…”
Section: Existed Fire Detection Technologies In China Road Tunnelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each sense cable of the system is required to cover two traffic lanes in the tunnels. Many researches have been conducted to study their capability and limitation in tunnel environments [29][30][31][32]. Test and operation results show that the linear heat detection systems:  Respond to a fire at its flame stage as the temperature in the tunnel raises, which may miss early warnings of the fire, depending on the fire type.…”
Section: Existed Fire Detection Technologies In China Road Tunnelsmentioning
confidence: 99%
“…Their maximum detection distance ranges from 40 to 50 m in the tunnels. Their performances in tunnel environments have also been substantially investigated [31,32,35]. Test and operation results show that flame detectors:  Respond to a fire at its flame stage, which may miss some early warnings of the fire, depending on the fire type.…”
Section: Existed Fire Detection Technologies In China Road Tunnelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Liu concluded that the detection time of the fire detection system under the longitudinal air condition depends on the fuel type, the size and location of the fire, the velocity of the air flow and the detection method [1]. Marty Ahrens counts the performance of the American home smoke alarm system [2].…”
Section: Introductionmentioning
confidence: 99%
“…Liu presented the results of the full-scale experiments conducted in a laboratory tunnel facility under longitudinal airflow conditions. The performance of nine fire detection systems representing five types of the fire detection technologies for road tunnel applications was investigated using representative tunnel fire scenarios [6]. Marty Ahrens provided background about smoke alarms in the general population and in unreported fires by the findings from the Consumer Product Safety Commission's 2004 to 2005 Residential Fire Survey [7].…”
Section: Introductionmentioning
confidence: 99%